ASSOCIATION BETWEEN ANTICHOLINERGIC BURDEN AND FUNCTIONAL OUTCOMES (ADL AND IADL) IN OLDER ADULTS: A PROSPECTIVE OBSERVATIONAL STUDY - Rani Manju; Dilip Chandrasekaran; Linu P Mohan; Santhosh M Mathews4 (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Anticholinergic medications are widely prescribed in older adults to manage various chronic conditions. However, these drugs are associated with adverse outcomes, including functional decline.Objective: This study examined the association between cumulative anticholinergic burden and functional performance, specifically Activities of Daily Living (ADL) and Instrumental Activities of Daily Living (IADL), in an elderly population.Methods: A prospective observational study was conducted among 235 individuals aged ≥60 years at a tertiary care hospital. Anticholinergic burden was assessed using a validated scoring system. Functional outcomes were evaluated using the Katz Index for ADL and the Lawton–Brody scale for IADL at baseline, 6 months, and 1 year. Stratified analysis by age and gender was conducted, and statistical associations were evaluated using t-tests, regression models, and correlation coefficients.Results: 235 older adults were included in the analysis, with a mean age of 72.4 ± 7.8 years. Females comprised 59% of the cohort (n = 139), and males accounted for 41% (n = 96). The average number of medications per participant was 6.2 ± 2.1. Hypertension (76.6%), diabetes mellitus (64.3%), and osteoarthritis (48.1%) were the most common comorbidities.Participants were categorized into anticholinergic burden groups as follows: low burden (n = 71; 30.2%), moderate burden (n = 91; 38.7%), and high burden (n = 73; 31.1%). This distribution formed the basis for all group comparisons in subsequent analyses. Although the association between anticholinergic burden and functional decline was not statistically significant, a moderate inverse trend between burden score and IADL performance was identified. The highest burden groups consistently demonstrated lower functional independence.Conclusion: While no significant association was found between anticholinergic burden and functional scores, the observed patterns underscore the potential role of anticholinergic exposure in age-related functional deterioration. Routine burden assessments and deprescribing strategies may help mitigate risk in older adults.